Powder material for laminate molding and method for manufacturing molded product using the powder material
The use of a specific powder material composition for additive manufacturing, characterized by its carbide ceramic and metal content, addresses the challenge of achieving high mechanical strength in additive manufacturing products by suppressing the formation of brittle phases, thereby enhancing the mechanical properties of the resulting shaped objects.
Patent Information
- Application Number
- JP2023170499
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Current powder materials for additive manufacturing, particularly those made of tungsten carbide (WC) and cobalt (Co), face challenges in achieving high mechanical strength without cracking or chipping, due to the formation of brittle phases during the additive manufacturing process.
A powder material composition for additive manufacturing that includes carbide ceramics and a metal, with a metal content of 8 to 43% by volume, and a solid solubility of carbide ceramics with respect to the metal at 1250°C of 8% by mass or less, which suppresses the formation of fragile phases and enhances mechanical strength.
The proposed powder material effectively improves the mechanical strength of additive manufacturing products by preventing the formation of brittle phases, resulting in shaped objects with superior mechanical properties without the need for additional heat treatment.
Smart Images

Figure 2025060020000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a powder material for layered manufacturing, and also to a method for manufacturing a molded object using the powder material. [Background technology]
[0002] So-called three-dimensional modeling technology, which creates a molded object based on data of its three-dimensional shape (e.g., three-dimensional CAD data), has become widespread. One such modeling technology is an additive manufacturing method in which powder material is spread in thin layers, then bonded or sintered into a shape corresponding to the cross section of the molded object to be modeled, and these thin layers are sequentially stacked together. Traditionally, resin materials have been widely used as powder modeling materials used in additive manufacturing, but in recent years, development of powder materials for additive manufacturing made of metals or ceramics that can be used in additive manufacturing such as powder bed fusion (PBF) and laser powder deposition (LMD) has been progressing (see Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2015 / 194678 [Patent Document 2] JP 2017-113952 A [Patent Document 3] JP 2017-114716 A [Patent Document 4] JP 2017-115194 A Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, one of the development goals of powder materials for additive manufacturing made of inorganic materials such as metals and ceramics is the development of powder materials that can produce molded objects with high mechanical strength without cracks or chips. As a material that meets this goal, development of powder materials mainly composed of tungsten carbide (WC) and cobalt (Co) is underway. Tungsten carbide and cobalt are the raw materials for cemented carbide (WC-Co alloy) and are suitable as materials for manufacturing high-hardness molded objects by additive manufacturing. However, there is still room for improvement in the powder materials developed so far in order to further improve the mechanical strength of the additive manufactured objects.
[0005] In view of the above circumstances, an object of the present invention is to provide a powder material for additive manufacturing that can form an additive manufactured object having superior mechanical strength. [Means for solving the problem]
[0006] In order to achieve the above object, the present inventors have conducted detailed studies on the alloy structure of an additively molded product made of powder materials mainly composed of carbide ceramics and metals. As a result, they have found that the mechanical strength of the molded product can be improved by using an alloy composition that can suppress the formation of brittle phases in the molded product, and have completed the present invention.
[0007] In other words, the present invention is a powder material for additive manufacturing comprising a carbide ceramic and a metal, wherein the content of the metal is 8 to 43 volume % relative to the total amount of the carbide ceramic and the metal, and in the XRD spectrum of an object produced by additive manufacturing including laser light irradiation, the powder material for additive manufacturing does not contain any peaks other than those derived from the powder material before laser light irradiation.
[0008] The present invention also relates to a powder material for additive manufacturing comprising a carbide ceramic and a metal, wherein the content of the metal is 8 to 43 volume % relative to the total amount of the carbide ceramic and the metal, and the solid solubility of the carbide ceramic in the metal at 1250°C is 8 mass % or less. Effect of the Invention
[0009] According to the present invention, there is provided a powder material for additive manufacturing that can form an additive manufactured object having superior mechanical strength. [Brief description of the drawings]
[0010] [Figure 1] 1 is a simplified schematic diagram of a powder additive manufacturing apparatus according to an embodiment; FIG. [Figure 2-1] 1 shows XRD spectra of the powder materials produced in Examples 1 to 5 and objects produced using the powder materials after being irradiated with laser light. [Figure 2-2] 1 shows XRD spectra of powder materials produced in Comparative Examples 1 to 3 and objects produced using the powder materials after being irradiated with laser light. [Diagram 3] 4 is a SEM photograph showing a cross section of a molded product and a sintered body thereof produced using the powder materials according to Example 1 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One form of the present invention is a powder material for additive manufacturing comprising a carbide ceramic and a metal, the content of the metal being 8 to 43 volume % relative to the total amount of the carbide ceramic and the metal, and in an XRD spectrum of an object produced by additive manufacturing including laser light irradiation, the powder material for additive manufacturing contains no peaks other than those derived from the powder material before laser light irradiation.
[0012] One form of the present invention is a powder material for additive manufacturing comprising a carbide ceramic and a metal, wherein the content of the metal is 8 to 43 volume % relative to the total amount of the carbide ceramic and the metal, and the solid solubility of the carbide ceramic in the metal at 1250°C is 8 mass % or less.
[0013] According to the present invention, there is provided a powder material for additive manufacturing that can form an additive manufactured object having superior mechanical strength.
[0014] When powder additive manufacturing such as powder bed fusion (PBF) and laser powder deposition (LMD) was carried out using a powder material mainly composed of tungsten carbide (WC) and cobalt (Co), which are widely used as powder materials for additive manufacturing, it was found that the irradiation energy of a laser beam or an electron beam during the manufacturing process caused the decomposition of WC and Co and the reaction between WC and Co due to the influence of melting and rapid solidification of WC and Co, resulting in decomposition products such as free carbon and reaction products between WC and Co. This made it possible for the η phase, which is a brittle layer, to be easily generated in the structure of the molded object. It was also found that the mechanical strength of the molded object decreased when a brittle phase such as the η phase was present in a high proportion in the molded object. In contrast, the powder material for additive manufacturing of this embodiment contains carbide ceramics and metal in a predetermined proportion, and does not contain any peaks other than those derived from the powder material before laser beam irradiation in the XRD spectrum of the molded object. In other words, it does not have any peaks derived from the brittle phase generated by the generation of reaction products due to the laser irradiation energy. Therefore, the mechanical strength of an object produced by additive manufacturing using the powder material can be improved. Moreover, the powder material for additive manufacturing of this embodiment contains a carbide ceramic and a metal in a predetermined ratio, and the solid solubility of the carbide ceramic in the metal is within a predetermined range. This makes it difficult for the carbide ceramic and the metal to come into contact with each other during additive manufacturing, suppressing their reaction, making it difficult for reactants to be produced, and making it difficult for a brittle phase to be produced. As a result, the mechanical strength of an object produced by additive manufacturing using the powder material can be improved.
[0015] Furthermore, when powder additive manufacturing is performed using a powder material mainly composed of tungsten carbide (WC) and cobalt (Co), which are widely used as powder materials for additive manufacturing, a reaction product between WC and Co (for example, Co3W3C) is generated as described above, but it was found that such a reaction product also causes a decrease in the mechanical strength of the molded object. In order to increase the mechanical strength of the molded object, an attempt was made to further heat treat the molded object and return the reaction product to WC and Co, but the WC grains grew during the heat treatment, and the effect of improving the mechanical strength was limited. In contrast, in the powder material of this embodiment, since a brittle phase is unlikely to occur in the molded object, excellent mechanical strength can be obtained even if no further heat treatment is performed after additive manufacturing. In addition, since the generation of the reaction product is suppressed, grain growth is unlikely to occur even if the molded object is further heat treated, and further improvement in the mechanical strength of the molded object can be achieved.
[0016] The powder material for additive manufacturing in this embodiment is such that in the XRD spectrum of a molded object obtained by additive manufacturing including laser light irradiation using the powder material for additive manufacturing, it does not contain any peaks other than those derived from the powder material before laser light irradiation.
[0017] In one embodiment, the powder material for additive manufacturing is used to produce a shaped object obtained by additive manufacturing including laser irradiation, and in an XRD spectrum of the shaped object that has not been subjected to further heat treatment, the XRD spectrum of the shaped object does not include peaks other than those derived from the powder material before laser irradiation. In one embodiment, the powder material for additive manufacturing is used to produce a shaped object (sintered body) after further heat treatment of the shaped object obtained by additive manufacturing including laser irradiation, and in an XRD spectrum of the shaped object (sintered body) after further heat treatment, the powder material for additive manufacturing is used to produce a shaped object (sintered body) after further heat treatment, the XRD spectrum of the shaped object (sintered body) does not include peaks other than those derived from the powder material before laser irradiation.
[0018] The powder material for additive manufacturing according to this embodiment is an object formed by additive manufacturing including laser beam irradiation, and it is preferable that the XRD spectrum of the object not subjected to further heat treatment does not contain any peaks other than those derived from the powder material before the laser beam irradiation. Moreover, when further heat treatment is performed, it is more preferable that the XRD spectrum of both the object not subjected to heat treatment and the object (sintered body) subjected to heat treatment does not contain any peaks other than those derived from the powder material before the laser beam irradiation.
[0019] Preferably, the powder material for additive manufacturing according to this embodiment is a powder material for additive manufacturing containing a carbide ceramic and a metal, the content of the metal being 8 to 43 volume % relative to the total amount of the carbide ceramic and the metal, the XRD spectrum of an object produced by additive manufacturing including laser beam irradiation does not contain any peaks other than those derived from the powder material before laser beam irradiation, and the solubility of the carbide ceramic in the metal at 1250°C is 8 mass % or less. With this configuration, the effect of the present invention can be obtained even more significantly.
[0020] Preferred embodiments of the present invention will be described below. Matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In the specification, the expression "X to Y" indicating a numerical range means "X or more and Y or less" unless otherwise specified.
[0021] <Definition> In this specification, the term "powder material" refers to a powdered material used in additive manufacturing. The powder material disclosed herein is a carbide ceramic / metal-containing powder material, i.e., a powder material for additive manufacturing whose main components are carbide ceramic and metal (i.e., a powder material for additive manufacturing whose maximum component in the entire powder material is carbide ceramic + metal by mass). For example, the powder material for additive manufacturing in this embodiment is composed of more than 50 mass% of the entire powder material by mass, which is composed of carbide ceramic and metal.
[0022] In this specification, the term "primary particle" refers to the smallest unit that can be identified as a granular material from the appearance among the morphological components that make up the powder material. Therefore, when the carbide ceramic / metal-containing powder material disclosed herein contains secondary particles (e.g., granulated particles), the particles that make up the secondary particles can be called primary particles. Here, "secondary particles" refers to particulate matter (in the form of particles) in which primary particles are three-dimensionally bonded together and behave as a single grain. Granulated particles and granulated sintered particles that are sintered after granulation are typical examples of "secondary particles" as used here.
[0023] The term "bonding" as used here refers to two or more primary particles being directly or indirectly linked together, and includes, for example, bonding between primary particles due to a chemical reaction, bonding between primary particles attracting each other due to simple adsorption, bonding utilizing the anchor effect of allowing an adhesive or the like to penetrate into the unevenness of the primary particle surface, bonding between primary particles utilizing the effect of attraction due to static electricity, and bonding in which the surfaces of primary particles are melted and integrated together.
[0024] In addition, in this specification, the term "raw material particles" refers to particles that constitute the powder in the raw material stage used to form the powder material disclosed herein.
[0025] In this specification, unless otherwise specified, the "average particle size" of a powder material refers to the average particle size at 50% of the cumulative value in the volume-based particle size distribution measured by a particle size distribution measuring device based on the laser scattering and diffraction method (50% volume average particle size; D 50)
[0026] <Composition of powder material> As mentioned above, the powder material disclosed herein is a ceramic carbide / metal-containing powder material that includes a ceramic carbide and a metal.
[0027] (Carbide ceramics) The carbide ceramics are not particularly limited as long as the shaped product using them shows a predetermined XRD spectrum or has a predetermined solid solubility in the metal described below. The carbide ceramics are not particularly limited, but include vanadium carbide (VC), niobium carbide (NbC), tantalum carbide (TaC), titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), silicon carbide (SiC), boron carbide (B4C), and the like. The carbide ceramics may be a composite carbide containing two or more metals. The carbide ceramics may contain any one type alone, or may contain two or more types in combination.
[0028] In a preferred embodiment, the carbide ceramic has a standard enthalpy of formation of -90 kJ / mol or less. This makes it difficult for the carbide ceramic to react with the metal in a rapid solidification process in which both the carbide ceramic and the metal are melted, such as in additive manufacturing. This makes it possible to prevent the reaction product between the carbide ceramic and the metal from causing a decrease in the performance of the molded product. The standard enthalpy of formation of the carbide ceramic is more preferably -95 kJ / mol or less, and even more preferably -100 kJ / mol or less. The lower limit of the standard enthalpy of formation of the carbide ceramic is not particularly limited, but is, for example, -250 kJ / mol or more. Examples of carbide ceramics having a standard enthalpy of formation of -90 kJ / mol or less include TiC (-185 kJ / mol), VC (-102 kJ / mol), ZrC (-203 kJ / mol), NbC (-139 kJ / mol), TaC (-146 kJ / mol), etc. When two or more types of carbide ceramics are used in combination, it is preferable that the standard enthalpy of formation of at least one type of carbide ceramic is in the above range, and it is more preferable that the standard enthalpy of formation of all of the carbide ceramics is in the above range.
[0029] The standard enthalpy of formation of carbide ceramics can be determined from the value given in the 5th Revised Edition of the Basic Chemistry Handbook, edited by the Chemical Society of Japan, published by Maruzen Publishing (February 2004).
[0030] In a preferred embodiment, the melting point of the carbide ceramic is 2700°C or higher. This makes it difficult for the carbide ceramic to react with the metal in a rapid solidification process in which both the carbide ceramic and the metal are melted, such as in additive manufacturing. This makes it possible to prevent the reaction product between the carbide ceramic and the metal from causing a decrease in the performance of the molded object. The melting point of the carbide ceramic is more preferably 2750°C or higher, and even more preferably 2800°C or higher. The upper limit of the melting point of the carbide ceramic is not particularly limited, but is, for example, 4000°C or lower, preferably 3950°C or lower, and more preferably 3900°C or lower. Within the above range, the molded object can be manufactured more efficiently by additive manufacturing. Examples of carbide ceramics having a melting point of 2700° C. or higher include TiC (3250° C.), VC (2830° C.), ZrC (3180° C.), NbC (3500° C.), HfC (3900° C.), TaC (3880° C.), etc. When two or more types of carbide ceramics are used in combination, it is preferable that at least one type of carbide ceramic has a melting point within the above range, and it is more preferable that all of the carbide ceramics have melting points within the above range.
[0031] The melting point of carbide ceramics can be determined from the values given in "Cemented Carbide and Sintered Hard Materials: Fundamentals and Applications" edited by Suzuki Hisashi, published by Maruzen Publishing (February 1986).
[0032] In a preferred embodiment, the carbide ceramics is one or more compounds selected from the group consisting of carbides of Group 4 elements and carbides of Group 5 elements. Examples of Group 4 elements include Ti, Zr, Hf, etc., and examples of carbides of Group 4 elements include TiC, ZrC, HfC, etc. Examples of Group 5 elements include V, Nb, Ta, etc., and examples of carbides of Group 5 elements include VC, NbC, TaC, etc. By using one or more compounds selected from the group consisting of carbides of Group 4 elements and carbides of Group 5 elements as the carbide ceramics, a shaped product with higher hardness can be obtained.
[0033] In the powder material for additive manufacturing of this embodiment, the ratio of the total amount of the carbide of the 4th group element and the 5th group element to the total amount of the carbide ceramics is, for example, 40% by mass or more, preferably 50% by mass or more, more preferably more than 50% by mass, even more preferably 55% by mass or more, even more preferably 60% by mass or more, even more preferably 65% by mass or more, even more preferably 70% by mass or more, even more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 97% by mass or more, even more preferably 99% by mass or more, and even more preferably 100% by mass. In one embodiment, the carbide ceramics are composed of only one or more compounds selected from the group consisting of carbides of the 4th group element and carbides of the 5th group element.
[0034] As the carbide ceramic powder consisting of raw material particles of carbide ceramics, which is the raw material of the powder material of this embodiment, various carbide ceramic powder materials commercially available for forming cemented carbide can be used. For example, 50 ) is 0.05 to 10 μm, preferably 0.1 to 8 μm, and more preferably 0.2 to 5 μm. By using a carbide ceramic powder made of such carbide ceramic raw material particles, a denser shaped product can be manufactured.
[0035] (metal) There are no particular limitations on the metal, so long as the shaped article using the metal exhibits a predetermined XRD spectrum or the solubility of the carbide ceramic is a predetermined value. Examples of the metal include magnesium (Mg), aluminum (Al), titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), gold (Au), silver (Ag), platinum (Pt), iridium (Ir), bismuth (Bi), niobium (Ni), molybdenum (Mo), tin (Sn), tungsten (W), lead (Pb), and alloys thereof. Any one of these metals may be contained alone, or two or more may be contained in combination. Among them, from the viewpoint of obtaining a shaped article with higher strength, the metal is preferably one or more selected from the group consisting of Co, Ni, and Fe, and more preferably Co or Ni.
[0036] In the powder material according to this embodiment, the XRD spectrum of an object produced by additive manufacturing including laser irradiation using the powder material does not contain any peaks other than those derived from the powder material before laser irradiation, or the solubility of the carbide ceramic in metal at 1250°C is 8 mass% or less. Here, the value of the solid solubility is the percentage value of the mass of the carbide ceramic that can be dissolved in unit mass of metal.
[0037] There is no particular limitation on the means for obtaining a powder material that produces a molded product that exhibits a predetermined XRD spectrum, but this can be achieved, for example, by selecting a carbide ceramic and a metal such that the solid solubility of the carbide ceramic in the metal at 1250° C. is 8 mass % or less. This makes it difficult for the carbide ceramic and the metal to react during additive manufacturing, and therefore makes it difficult for peaks other than those derived from the raw powder material to appear in the XRD spectrum of the molded product.
[0038] If the solubility of the carbide ceramic in the metal at 1250°C exceeds 8% by mass, a reaction product between the carbide ceramic and the metal is generated during additive manufacturing, which may reduce the performance of the molded product. The solubility of the carbide ceramic in the metal at 1250°C is preferably 7% by mass or less, more preferably less than 7% by mass, and even more preferably 6% by mass or less. The lower limit of the solubility of the carbide ceramic in the metal at 1250°C is not particularly limited, but is, for example, 0.1% by mass or more, preferably 0.5% by mass or more, and more preferably 1% by mass or more. Examples of such combinations of carbide ceramics and metals include TiC / Co (1 mass%), TiC / Ni (5 mass%), TiC / Fe (0.5 mass%), VC / Co (6 mass%), VC / Ni (7 mass%), VC / Fe (3 mass%), NbC / Co (5 mass%), NbC / Ni (3 mass%), NbC / Fe (1 mass%), TaC / Co (3 mass%), TaC / Ni (5 mass%), TaC / Fe (0.5 mass%), etc. Here, the solid solubility of carbide ceramics in metals is the value of the solid solubility of a single carbide ceramic (however, those with common constituent elements such as VC and V4C3 are considered to be a single carbide ceramic) in a single metal.
[0039] Here, the solid solubility value of carbide ceramics in metals at 1250°C is the value described in FW Glasser: Met. Progr., 67 (1955) 77-82. For example, compounds with common constituent elements, such as VC and V4C3, can be considered to have the same solid solubility value.
[0040] In addition, when two or more types of carbide ceramics are used in combination and / or when two or more types of metals are used in combination, the solid solubility value at 1250°C of a component constituting more than 50 mass% of the entire carbide ceramics is 8 mass% or less with respect to a component constituting more than 50 mass% of the entire metal. When the mass ratio of the carbide ceramic with the highest mass ratio is 50 mass% or less of the entire carbide ceramics, each of the carbide ceramics may have the above solid solubility value. Similarly, when the mass ratio of the metal with the highest mass ratio is 50 mass% or less of the entire metals, each of the metals may have the above solid solubility value. When the mass ratio of the carbide ceramic with the highest mass ratio is 50 mass% or less and the mass ratio of the metal with the highest mass ratio is 50 mass% or less, each of the combinations of all the carbide ceramics and all the metals may have the above solid solubility value.
[0041] More preferably, in all combinations of carbide ceramics and metals contained in the powder material, the solid solubility of the carbide ceramics in the metal at 1250° C. is 8 mass % or less.
[0042] In one embodiment, the powder material for additive manufacturing includes cobalt and a carbide ceramic having a solid solubility in cobalt of 8% by mass or less at 1250° C. In one embodiment, the powder material for additive manufacturing includes nickel and a carbide ceramic having a solid solubility in nickel of 8% by mass or less at 1250° C.
[0043] In addition, as the metal powder made of raw metal particles used in the production of the powder material disclosed herein, metal powders used in powder metallurgy or for the production of cemented carbide materials can be used without any particular restrictions. 50 A metal powder having a particle size range of about 1 μm or more (eg, 2 μm or more) and 10 μm or less (eg, 5 μm or less) can be preferably used.
[0044] In the powder material of this embodiment, the metal content is 8 to 43 volume % with respect to the total amount of the carbide ceramics and the metal. If the metal content is less than 8 volume %, the molten metal cannot sufficiently wet and spread on the surface of the carbide ceramic particles during layered granulation, and a dense shaped product cannot be manufactured. As a result, a shaped product with high hardness cannot be obtained. On the other hand, if the metal content exceeds 43 volume %, the content of the carbide ceramics becomes relatively small, and therefore a shaped product with high hardness cannot be obtained. The metal content is preferably 10 to 40 volume %, more preferably 15 to 35 volume %, and even more preferably 15 to 30 volume % with respect to the total amount of the carbide ceramics and the metal. The metal content in the powder material of this embodiment does not change from the stage of preparation to the process of sintering and granulation, both in terms of mass and volume.
[0045] In one embodiment, the metal content may be 8 to 43 volume % relative to the total amount of powder material, preferably 10 to 40 volume %, more preferably 15 to 35 volume %, and even more preferably 20 to 30 volume %.
[0046] In one embodiment, the content of the metal is preferably 5 to 45 mass%, more preferably 10 to 45 mass%, and even more preferably 15 to 40 mass%, based on the total amount of the carbide ceramic and the metal. In one embodiment, the content of the metal is preferably 5 to 45 mass%, more preferably 10 to 45 mass%, and even more preferably 15 to 40 mass%, based on the total amount of the powder material.
[0047] (optional ingredient) The powder material of this embodiment may contain optional components other than carbide ceramics and metals. The optional components include carbon materials (e.g., particulate solid carbon materials). Examples of such solid carbon materials include graphite, carbon black (acetylene black, ketjen black, etc.), activated carbon, carbon fibers (PAN-based carbon fibers, pitch-based carbon fibers, graphite fibers, etc.), and nanocarbons (carbon nanotubes, fullerenes, graphene, diamond particles, etc.). In addition, the optional components may include binders, dispersants, surfactants, inorganic pigments, organic pigments, etc. The binders, dispersants, surfactants, inorganic pigments, and organic pigments are not particularly limited, and known materials may be appropriately selected.
[0048] The content (mass basis) of the carbide ceramics in the entire powder material is not particularly limited, but the content of the carbide ceramics is preferably more than 50 mass%, more preferably 55 mass% or more, and even more preferably 60 mass% or more of the entire powder material, and the content of the carbide ceramics is preferably 95 mass% or less, and more preferably 90 mass% or less of the entire powder material.
[0049] In a preferred embodiment, the content of one or more compounds selected from the group consisting of carbides of Group 4 elements and carbides of Group 5 elements is preferably more than 50 mass% of the entire powder material, and more preferably 60 mass% or more. In a preferred embodiment, the content of carbides containing Group 6 elements (WC, W2C, Co3W3C, Cr3W3, Cr7C3, Cr3C2, Mo2C, etc.) is preferably 5 mass% or less of the entire powder material, more preferably 3 mass% or less, even more preferably 1 mass% or less, and most preferably 0 mass%. This configuration makes it possible to more effectively suppress the generation of brittle phases, and makes it easier to obtain shaped objects with excellent mechanical strength.
[0050] The total amount of the carbide ceramics and the metal is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more (upper limit 100% by mass) of the entire powder material. This configuration makes it possible to more effectively suppress the generation of brittle phases, and makes it easier to obtain shaped products with excellent mechanical strength.
[0051] The average particle diameter (50% volume average particle diameter; D 50 ) is not particularly limited and can be a size suitable for the specifications of the additive manufacturing device used. For example, the average particle size of the powder material can be a size suitable for supplying the powder material in additive manufacturing. The upper limit of the average particle size of the powder material may exceed 200 μm, for example, when it is larger, but is typically 200 μm or less. The upper limit of the average particle size of the powder material is preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 40 μm or less. As the average particle size of the powder material decreases, the filling rate of the powder material in, for example, the modeling area can be improved. As a result, the density of the three-dimensional object to be modeled can be suitably increased. In addition, the surface roughness (Ra) of the three-dimensional object to be modeled can be reduced, and the effect of improving the dimensional accuracy can be obtained. In addition, the lower limit of the average particle size of the powder material is not particularly limited as long as it is within a range that does not affect the flowability of the powder material. However, when the handling during formation of the powder material and the fluidity of the powder material are taken into consideration, the lower limit of the average particle size can be set to 1 μm or more, preferably 5 μm or more, and more preferably 10 μm or more. As the average particle size of the powder material increases, the fluidity of the powder material improves. As a result, the powder material can be smoothly supplied to the molding device, and the finished three-dimensional object to be manufactured is favorable, which is preferable. Although not particularly limited, from the viewpoint of the finished three-dimensional object of the powder material according to this embodiment, the value obtained by dividing the cumulative 97% particle size by the cumulative 3% particle size may be 2 or more and 6 or less, and preferably 3 or more and 5 or less. The average particle size (50% volume average particle size; D 50), the cumulative 97% particle size and the cumulative 3% particle size can be determined by the method described in the Examples below.
[0052] The strength of the powder material (for example, granulated sintered particles) according to this embodiment (hereinafter referred to as "granule strength") is 1 kgf / mm 2 It is preferable that the resistance is 5kgf / mm or more. 2 More preferably, it is 10 kgf / mm 2 or more (e.g., 20 kgf / mm 2 It is particularly preferable that the granule strength is 500 kgf / mm or more. This makes it possible to effectively prevent the granulated sintered powder from collapsing or scattering due to the energy used for modeling. As a result, the supply of powder material to the modeling area is stabilized, making it possible to model a high-quality model without unevenness. On the other hand, from the viewpoint of making it easy to sufficiently melt the powder material, the granule strength is preferably 500 kgf / mm 2 It is preferable that the strength is less than 300 kgf / mm 2 More preferably, it is 200 kgf / mm 2 More preferably, it is 100 kgf / mm 2 Less than (for example, 50 kgf / mm 2 The granule strength of the powder material (for example, the granulated and sintered particles described later) can be determined by the method described in the Examples described later.
[0053] The bulk density of the powder material according to the present embodiment (for example, granulated and sintered particles) is not particularly limited, but is, for example, 0.5 to 5 g / cm 3 Within the above range, the filling rate of the powder material in the modeling area can be improved. As a result, the density of the three-dimensional object to be modeled can be suitably increased. In addition, the powder material is easy to handle when formed and has excellent flowability. The bulk density of the powder material (for example, the granulated sintered particles described later) can be determined by the method described in the Examples described later.
[0054] The powder material according to the present embodiment (for example, granulated sintered particles) is not particularly limited, but preferably has an angle of repose of less than 39°. The angle of repose can be one of the indices that have been widely adopted to indicate the fluidity of a powder. For example, the angle of repose can be an index that can actually reflect the spontaneous fluidity of the powder material when it is transported in a supply device and a molding device. Therefore, by setting the angle of repose to be small, a powder material with high fluidity can be realized. In addition, the powder material can be a powder material that can produce a homogeneous three-dimensional object with higher productivity. There is no particular limit to the lower limit of the angle of repose, but from the viewpoint of making the powder material less likely to scatter and facilitating the control of the supply amount of the powder material, the angle of repose is preferably 20° or more. The angle of repose of the powder material (for example, the granulated sintered particles described later) can be determined by the method described in the examples described later.
[0055] <Preparation of powder materials> The powder material disclosed herein can be prepared, for example, by mixing raw material particles made of carbide ceramics and raw material particles made of a metal, optionally with optional components. A material made of such a mixed powder is a typical example of the carbide ceramic / metal-containing powder material disclosed herein.
[0056] However, a more suitable powder material is one that is composed of granulated and sintered particles containing the above-mentioned carbide ceramics and metal. Typically, the powder material is made by mixing and granulating raw material particles (primary particles) of each component, and then sintering the mixture to form primary particles, which are then bonded three-dimensionally with gaps between the primary particles. This makes it possible to more effectively suppress the formation of a brittle phase, and to obtain a molded product with superior mechanical strength. Hereinafter, an example of a granulation and sintering method for suitably producing such granulated and sintered particles will be described, but the method is not limited to this method.
[0057] <Production of Granulated Sintered Particles> The granulation sintering method is a method in which raw material particles are granulated into the form of secondary particles, and then sintered to bond (sinter) the raw material particles together. In such a granulation sintering method, granulation can be carried out using a granulation method such as dry granulation or wet granulation. Examples of the granulation method include a rolling granulation method, a fluidized bed granulation method, a stirring frame granulation method, a crushing granulation method, a melt granulation method, a spray granulation method, and a microemulsion granulation method. Among them, a preferred granulation method is the spray granulation method.
[0058] According to the spray granulation method, for example, the powder material can be manufactured by the following procedure. That is, first, raw material particles of the type corresponding to each of the carbide ceramics and the metal are prepared, and the surface thereof is stabilized by a protective agent or the like as necessary. Then, the raw material particles are dispersed in an appropriate solvent together with, for example, a binder as an optional component and / or spacer particles made of an organic material, to prepare a spray liquid. Dispersion of the raw material particles in the solvent can be carried out using, for example, a mixer such as a homogenizer or a blade stirrer, a disperser, or the like. Then, droplets are formed from the spray liquid using an ultrasonic atomizer or the like, and the droplets are placed on an air flow and passed through a spray drying device (spray dryer), to form granulated particles.
[0059] The obtained granulated particles are introduced into a specified sintering furnace and sintered to obtain a powder material consisting of granulated and sintered particles in the form of secondary particles in which primary particles are bonded with gaps between them. Note that the primary particles may have substantially the same size and shape as the raw material particles, or the raw material particles may be grown and bonded by sintering.
[0060] In the above manufacturing process, when the droplets are dried, the raw material particles and the binder are in a uniform mixed state, and the raw material particles are bound by the binder to form the mixed particles. When spacer particles are further used, the raw material particles and the spacer particles are in a uniform mixed state and bound by the binder to form the mixed particles. Then, when the mixed particles are fired, the binder (and the spacer particles) disappear (burn out), and the raw material particles are sintered to form secondary particles in which the primary particles are bound with gaps between them.
[0061] During sintering, some of the raw material particles may become liquid depending on their composition and size, and contribute to bonding with other particles. Therefore, the average particle size of the primary particles may be larger than that of the raw material particles of the starting material. The average particle size of the secondary particles and primary particles, and the size and ratio of the gaps formed between the primary particles can be designed according to the desired shape of the secondary particles. Similarly, the granular strength, bulk density, and angle of repose of the secondary particles can also be designed according to the desired shape of the secondary particles.
[0062] In the above manufacturing process, the concentration of the raw material particles in the spray liquid is preferably 10 to 40% by mass. Examples of the binder to be added include carboxymethyl cellulose (CMC) and polyvinylpyrrolidone (PVP). The binder to be added is preferably adjusted to a ratio of 0.05 to 10% by mass (for example, 1 to 5% by mass) relative to the mass of the raw material particles. The sintering environment is not particularly limited, but may be in air, vacuum, or an inert gas atmosphere, and is preferably sintered at a temperature of 600°C to 1600°C. In particular, when spacer particles, binders, etc. made of organic materials are used, sintering may be performed in an atmosphere containing oxygen in order to remove the organic materials in the granulated particles. If necessary, the produced secondary particles may be crushed and classified.
[0063] <XRDスペクトル> In the powder material according to one embodiment of the present invention, in the XRD spectrum of a molded object produced by additive manufacturing including laser irradiation, there is no peak other than the peak derived from the powder material before laser irradiation. A specific embodiment of additive manufacturing including laser irradiation is as described below. Examples of peaks other than the peak derived from the powder material before laser irradiation include peaks resulting from decomposition of carbide ceramics accompanying melting and rapid solidification of carbide ceramics and metals, reaction products between carbide ceramics and metals, free carbon, and the generation of brittle phases resulting from these. By suppressing the generation of such peaks, a molded object that is dense and has excellent mechanical strength can be obtained. For example, a method for obtaining such a powder material includes selecting a combination of carbide ceramics and metals that are unlikely to cause such a reaction. For example, a combination of carbide ceramics and metals can be selected such that the solid solubility of the carbide ceramics in the metal at 1250°C is 8% by mass or less.
[0064] <Additive Manufacturing> The powder material of this embodiment can be used for additive manufacturing, and an additively manufactured object can be manufactured by additive manufacturing. That is, one embodiment of the present invention is a method for manufacturing a molded object, which is characterized by performing additive manufacturing using the powder material for additive manufacturing of this embodiment. According to the method of this embodiment, a molded object having excellent mechanical properties can be manufactured.
[0065] Typical examples of such additive manufacturing methods include laser powder deposition (also called laser metal deposition; LMD) and powder bed fusion (PBF). Powder bed fusion (PBF) includes selective laser melting (SLM), which uses a laser as the irradiation energy, and electron beam melting (EBM), which uses an electron beam as the irradiation energy.
[0066] Laser powder cladding is a technology that provides powder material to a desired part of a structure, and then irradiates the powder material with a laser beam to melt and solidify the powder material, thereby cladding the part (i.e., manufacturing a shaped object). By using this method, for example, when physical deterioration such as wear occurs in a structure, the material that constitutes the structure or the reinforcing material can be supplied as a powder material to the deteriorated part, and the powder material can be melted and solidified to cladding the deteriorated part.
[0067] Powder bed fusion is a process in which a laser or electron beam is scanned across a layer of deposited powder material based on slice data created from a design drawing, and the powder layer is melted and solidified into the desired shape. This process is repeated for each cross section (slice data), allowing the creation of three-dimensional structures.
[0068] In a preferred embodiment, the additive manufacturing includes melting and solidifying the powder material by irradiating it with a laser beam. This makes it possible to more efficiently obtain a molded object having excellent mechanical strength. In a preferred embodiment, the additive manufacturing is performed by a powder bed fusion method using a laser as the irradiation energy.
[0069] An example of a method for manufacturing a molded object by powder additive manufacturing using a powder material disclosed herein will be described with reference to FIG. 1. FIG. 1 is a simplified diagram of an additive manufacturing apparatus for powder additive manufacturing. As shown in this figure, the additive manufacturing apparatus is roughly configured to include a stacking area 10, which is a space where additive manufacturing is performed, a stock 12 for storing the powder material, a wiper 11 for assisting in the supply of the powder material to the stacking area 10, and a solidification means 13 for solidifying the powder material (a laser oscillator such as a carbon dioxide laser or a YAG laser, or an energy irradiation means such as a beam irradiator). Note that "solidification" includes directly bonding particles (e.g., secondary particles) constituting the powder material to each other by melting and solidifying, and fixing the shape to a predetermined cross-sectional shape.
[0070] The stacking area 10 typically has a printing space with an enclosed periphery below the printing surface, and is equipped with a lifting table 14 that can rise and fall within this printing space. This lifting table 14 can be lowered by a predetermined thickness Δt1 at a time, and the target object is printed on this lifting table 14. The stock 12 is disposed beside the stacking area 10, and is equipped with, for example, a bottom plate (lifting table 14) that can be raised and lowered by a cylinder or the like within a storage space with an enclosed periphery. By raising the bottom plate, a predetermined amount of powder material can be supplied (extruded) to the printing surface.
[0071] In this layered modeling apparatus, the powder material layer 20 having a predetermined thickness Δt1 can be prepared by supplying the powder material layer 20 to the lamination area 10 in a state where the lift table 14 is lowered by a predetermined thickness Δt1 from the modeling surface. At this time, the wiper 11 is caused to scan the modeling surface, whereby the powder material extruded from the stock 12 is supplied onto the lamination area 10 and the surface of the powder material is flattened to form a homogeneous powder material layer 20. Then, for example, the powder material is melted or sintered into a desired cross-sectional shape by irradiating the first layer of powder material layer 20 with energy such as a laser beam or an electron beam via the solidification means 13 only to a solidified region corresponding to the slice data of the first layer, thereby forming the first layer of solidified powder layer 21.
[0072] Next, the lift table 14 is lowered by a predetermined thickness Δt1, and the powder material is supplied again, and the wiper 11 is smoothed to form the second powder material layer 20. Then, the powder material is solidified by irradiating energy via the solidification means 13 only to the solidification area of the powder material layer 20 corresponding to the slice data of the second layer, thereby forming the second powder solidification layer 21. At this time, the second powder solidification layer 21 and the first powder solidification layer 21, which is the lower layer, are integrated to form a laminate up to the second layer. Subsequently, the lift table 14 is lowered by a predetermined thickness Δt1 to form a new powder material layer 20, and energy is irradiated via the solidification means 13 to form the powder solidification layer 21 only in the required place. In this way, the additive manufacturing device can manufacture the desired three-dimensional object based on slice data created from a design drawing (3D CAD data) prepared in advance by repeating this process.
[0073] As described above, the powder material disclosed herein suppresses the formation of brittle phases in the additive manufacturing process, making it possible to produce three-dimensional cemented carbide ceramic-metal-based objects with high hardness and minimal cracking or chipping.
[0074] The three-dimensional object formed by the above steps may be used as a three-dimensional cemented carbide object as it is, but in a preferred embodiment, the three-dimensional object formed by the above steps is subjected to a heat treatment. The temperature of the heat treatment is not particularly limited, but is, for example, 1200°C or higher and 1500°C or lower. The heat treatment is preferably performed under reduced pressure, but is not particularly limited. The pressure during the heat treatment is also not particularly limited, but is, for example, 1 Pa or higher and 100 Pa or lower. The time of the heat treatment is not particularly limited, but is, for example, 0.1 to 50 hours, preferably 1 to 10 hours. The heat treatment may be performed continuously or intermittently, but the total heat treatment time is preferably within the above range. The three-dimensional object is sintered and densified by this heat treatment.
[0075] The three-dimensional object after the heat treatment may be further subjected to hot isostatic pressing (HIP). Hot isostatic pressing (HIP) is a technique for pressurizing an object at high temperature and high pressure. For example, the three-dimensional object after the heat treatment may be air-cooled to a temperature close to room temperature and then subjected to HIP.
[0076] The heating temperature of the HIP is, for example, 1200°C or higher and 1400°C or lower, and preferably 1300°C or higher and 1400°C or lower. The applied pressure of the HIP is preferably sufficiently higher than the pressure of the above-mentioned heat treatment, for example, 50 MPa or higher and 180 MPa or lower. The treatment time of the HIP is, for example, 1 hour or higher and 5 hours or lower. The HIP is performed in a state where the three-dimensional object is placed in an inert gas atmosphere such as argon (Ar), although there is no particular limitation. By further performing HIP on the three-dimensional object after the heat treatment, the three-dimensional object can be further densified and the strength can be increased.
[0077] That is, one aspect of the present invention is an object produced by additive manufacturing using the powder material for additive manufacturing of the present aspect. In a preferred embodiment, the additive manufacturing includes laser light irradiation. In a preferred embodiment, the additive manufacturing includes melting and solidifying the powder material by laser light irradiation.
[0078] The object formed by additive manufacturing using the powder material for additive manufacturing of this embodiment may be an object formed by additive manufacturing including laser light irradiation, or may be a sintered body formed by further heat-treating the object. According to one embodiment, the object is an object that has not been heat-treated after additive manufacturing including laser light irradiation.
[0079] The present invention encompasses the following aspects and configurations. 1. A powder material for additive manufacturing comprising a carbide ceramic and a metal, The content of the metal is 8 to 43 volume % based on the total amount of the carbide ceramic and the metal, a powder material for additive manufacturing, which does not contain any peaks other than peaks derived from the powder material before being irradiated with laser light in an XRD spectrum of an object produced by additive manufacturing including laser light irradiation; 2. A powder material for additive manufacturing comprising a carbide ceramic and a metal, The content of the metal is 8 to 43 volume % based on the total amount of the carbide ceramic and the metal, a powder material for additive manufacturing, in which the carbide ceramic has a solid solubility in the metal at 1250°C of 8% by mass or less; 3. The powder material for additive manufacturing according to 1 or 2 above, wherein the standard enthalpy of formation of the carbide ceramic is -90 kJ / mol or less; 4. The powder material for additive manufacturing according to any one of 1. to 3. above, wherein the melting point of the carbide ceramic is 2700°C or higher; 5. The powder material for additive manufacturing according to any one of 1. to 4. above, wherein the carbide ceramic is one or more compounds selected from the group consisting of carbides of Group 4 elements and carbides of Group 5 elements; 6. The powder material for additive manufacturing according to any one of 1. to 5. above, wherein the metal is one or more selected from the group consisting of cobalt, nickel, and iron; 7. The powder material for additive manufacturing according to any one of 1. to 6. above, which is composed of granulated and sintered particles in which the carbide ceramic and the metal are mixed; 8. A method for manufacturing a molded object, comprising carrying out additive manufacturing using the powder material for additive manufacturing according to any one of 1. to 7. above; 9. A method for manufacturing a molded object according to claim 8, wherein the additive manufacturing comprises melting and solidifying the powder material by irradiating it with laser light. EXAMPLES
[0080] Below, examples relating to the powder material and the production of a shaped object disclosed herein will be described, but it is not intended that the present technology be limited to those shown in the following examples.
[0081] <Preparation of powder materials> Example 1 The raw material powder has an average particle diameter (D 50 ) of about 1 μm and titanium carbide (TiC) powder with an average particle diameter (D 50 Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. TiC powder and Co powder were mixed so that 39 mass% (26.4 volume%) of the total amount of TiC powder and Co powder was Co powder. Then, 99 parts by mass of the mixture of TiC powder and Co powder and 1 part by mass of CMC were blended, and the blended powder obtained was wet-mixed and then granulated by a spray dryer. The obtained granulated particles were sintered to produce a powder material consisting of granulated and sintered particles (secondary particles) according to this embodiment.
[0082] The melting point of TiC is 3250°C, the standard enthalpy of formation of TiC is -185 kJ / mol, and the solid solubility of TiC in Co at 1250°C is 1 mass%.
[0083] Here, in each of the examples and comparative examples, the melting point of the carbide ceramics was determined from the value described in "Cemented Carbide and Sintered Hard Materials: Fundamentals and Applications," edited by Suzuki Hisashi, Maruzen Publishing (February 1986). The standard enthalpy of formation of the carbide ceramics was determined from the value described in "Chemical Handbook: Basics, 5th Revised Edition," edited by the Chemical Society of Japan, Maruzen Publishing (February 2004). The solid solubility of carbide ceramics in metals at 1250°C was determined from the value described in FW Glasser: Met. Progr., 67 (1955) 77-82.
[0084] Example 2 The raw material powder has an average particle diameter (D 50 ) of about 0.2 μm and vanadium carbide (VC) powder with an average particle size (D 50 Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. VC powder and Co powder were mixed so that 36 mass% (26.4 volume%) of the total amount of VC powder and Co powder was Co powder. Then, 99 parts by mass of the mixture of VC powder and Co powder and 1 part by mass of CMC were mixed. Except for the above, the powder material according to this embodiment was manufactured by the same process as in Example 1.
[0085] The melting point of VC is 2830°C, the standard enthalpy of formation of VC is -102 kJ / mol, and the solid solubility of VC in Co at 1250°C is 6 mass%.
[0086] Example 3 The raw material powder has an average particle diameter (D 50 ) of about 5 μm and zirconium carbide (ZrC) powder with an average particle diameter (D 50 Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. ZrC powder and Co powder were mixed so that 32 mass% (26.4 volume%) of the total amount of ZrC powder and Co powder was Co powder. Then, 99 parts by mass of the mixture of ZrC powder and Co powder and 1 part by mass of CMC were mixed. Except for the above, the powder material according to this embodiment was manufactured by the same process as in Example 1.
[0087] The melting point of ZrC is 3180°C, and the standard enthalpy of formation of ZrC is -203 kJ / mol.
[0088] Example 4 The raw material powder has an average particle diameter (D 50 ) of about 2 μm and niobium carbide (NbC) powder with an average particle size (D 50 Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. NbC powder and Co powder were mixed so that 29 mass% (26.4 volume%) of the Co powder was the total amount of NbC powder and Co powder. Then, 99 parts by mass of the mixture of NbC powder and Co powder and 1 part by mass of CMC were mixed. Except for the above, the powder material according to this embodiment was manufactured by the same process as in Example 1.
[0089] The melting point of NbC is 3500°C, the standard enthalpy of formation of NbC is -139 kJ / mol, and the solid solubility of NbC in Co at 1250°C is 5 mass%.
[0090] Example 5 The raw material powder has an average particle diameter (D 50 ) of about 1.5 μm and tantalum carbide (TaC) powder with an average particle size (D 50 Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. TaC powder and Co powder were mixed so that 18 mass% (26.4 volume%) of the Co powder was the total amount of TaC powder and Co powder. Then, 99 parts by mass of the mixture of TaC powder and Co powder and 1 part by mass of CMC were mixed. Except for the above, the powder material according to this embodiment was manufactured by the same process as in Example 1.
[0091] The melting point of TaC is 3880°C, the standard enthalpy of formation of TaC is -146 kJ / mol, and the solid solubility of TaC in Co at 1250°C is 3 mass%.
[0092] Example 6 The raw material powder has an average particle diameter (D 50 ) of about 1 μm and titanium carbide (TiC) powder with an average particle diameter (D 50 Nickel (Ni) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. TiC powder and Ni powder were mixed so that 30 mass % (19.2 volume %) of the total amount of TiC powder and Ni powder was Ni powder. Then, 99 parts by mass of the mixture of TiC powder and Ni powder and 1 part by mass of CMC were blended, and the blended powder obtained was wet-mixed and then granulated by a spray dryer. The obtained granulated particles were sintered to produce a powder material consisting of granulated and sintered particles (secondary particles) according to this embodiment.
[0093] The solid solubility of TiC in Ni at 1250° C. is 5 mass %.
[0094] Comparative Example 1 The raw material powder has an average particle diameter (D 50 ) of about 2 μm and chromium carbide (Cr3C2) powder with an average particle diameter (D 50A cobalt (Co) powder having a particle size of about 3 μm was prepared. CMC was prepared as a binder. Cr3C2 powder and Co powder were mixed so that 32 mass% (26.4 volume%) of the Co powder was the total amount of the Cr3C2 powder and the Co powder. Then, 99 parts by mass of the mixture of Cr3C2 powder and Co powder and 1 part by mass of CMC were mixed. A powder material according to this comparative example was manufactured by the same process as in Example 1 except for the above.
[0095] The melting point of Cr3C2 is 1895°C, the standard enthalpy of formation of Cr3C2 is -81 kJ / mol, and the solid solubility of Cr3C2 in Co at 1250°C is 12 mass%.
[0096] Comparative Example 2 The raw material powder has an average particle diameter (D 50 Molybdenum carbide (Mo2C) powder with an average particle size (D 50 A cobalt (Co) powder having a particle size of about 3 μm was prepared. CMC was prepared as a binder. Mo2C powder and Co powder were mixed so that 26 mass% (26.4 volume%) of the Co powder was the total amount of Mo2C powder and Co powder. Then, 99 parts by mass of the mixture of Mo2C powder and Co powder and 1 part by mass of CMC were mixed. A powder material according to this comparative example was manufactured by the same process as in Example 1 except for the above.
[0097] The melting point of Mo2C is 2690°C, the standard enthalpy of formation of Mo2C is -25 kJ / mol, and the solid solubility of Mo2C in Co at 1250°C is 13 mass%.
[0098] Comparative Example 3 The raw material powder has an average particle diameter (D 50 ) of about 2 μm and tungsten carbide (WC) powder with an average particle size (D 50Cobalt (Co) powder with a particle size of about 3 μm was prepared. CMC was prepared as a binder. WC powder and Co powder were mixed so that 17 mass% (26.4 volume%) of the Co powder was the total amount of the WC powder and the Co powder. Then, 99 parts by mass of the mixture of WC powder and Co powder and 1 part by mass of CMC were mixed. Aside from the above, the powder material according to this comparative example was manufactured by the same process as in Example 1.
[0099] The melting point of WC is 2600°C, the standard enthalpy of formation of WC is -41 kJ / mol, and the solid solubility of WC in Co at 1250°C is 22 mass%.
[0100] In each of the examples and comparative examples, the average particle size of the raw material powder (average particle size of primary particles) is the particle size at 50% of the cumulative value in the volume-based particle size distribution measured by a particle size distribution measuring device based on a laser diffraction / scattering method (50% volume average particle size; D 50 ) was used. For powders with an average primary particle diameter of less than 1 μm, the value calculated as the diameter of spherical particles (sphere equivalent diameter) calculated from the specific surface area was used. The average primary particle diameter (Dave) can be calculated based on the formula: Dave = 6 / (ρSm), where Sm is the specific surface area of the raw powder and ρ is the density. The specific surface area can be calculated by the BET method from the amount of gas adsorption such as N2 measured by the continuous flow method using a specific surface area measuring device (FlowSorbII 2300, manufactured by Micromeritics Co., Ltd.). This specific surface area can be measured in accordance with the "Method for measuring the specific surface area of powders (solids) by gas adsorption" specified in JIS Z8830:2013 (ISO9277:2010).
[0101] The volumetric particle size distribution of the powder materials (granulated and sintered particles) prepared in each Example and Comparative Example was measured using a commercially available particle size distribution measuring device based on the laser diffraction and scattering method. 50 and D. 97The column shows the cumulative 3% particle size, cumulative 50% particle size (average particle size), and cumulative 97% particle size from the small particle size side based on the obtained particle size distribution. The average particle size (D 50 ) was in the range of 25-30 μm, and most of the particles were in the range of 10-60 μm.
[0102] In addition, the powder materials (granulated sintered particles) prepared in each Example and Comparative Example were subjected to granule strength measurement using an electromagnetic force loading type compression tester. Specifically, 10 or more granulated sintered particles constituting the powder materials in each Example and Comparative Example were randomly sampled, and the arithmetic mean value of the breaking strength measured using a commercially available micro-compression tester (MCT-500: manufactured by Shimadzu Corporation) was used as the granule strength (kgf / mm 2 For the granulated and sintered particles, when the critical load obtained in the compression test is L [N] and the average particle diameter is d [mm], the breaking strength σ [MPa] of the granulated and sintered particles is calculated by the formula: σ = 2.8 × L / π / d 2 The granule strength (kgf / mm 2 ) are shown in the corresponding columns in Table 1.
[0103] The bulk density was measured for the powder materials (granulated sintered particles) prepared in each of the examples and comparative examples. The bulk density was measured according to the metal powder-apparent density measurement method specified in JIS Z2504:2012. Specifically, the bulk density was calculated by measuring the mass of the powder when the powder naturally flows out of an orifice with a diameter of 2.5 mm and fills a container of a predetermined capacity in a natural filling state. The bulk density was measured using a JIS bulk density measuring instrument for metal powders (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.). The results are shown in Table 1 below.
[0104] The repose angle was measured for the powder material (granulated sintered particles) prepared in each Example and Comparative Example. In this specification, the repose angle means the base angle calculated from the diameter and height of a cone-shaped deposit generated by dropping the powder material from a funnel of a certain height onto a horizontal substrate. The repose angle was measured in accordance with the provisions of JIS R 9301-2-2:1999 "Method of measuring physical properties of alumina powder-2: Repose angle". The results are shown in Table 1 below.
[0105] <Creating objects> Using the powder materials (granulated sintered particles) prepared in each Example and Comparative Example, a simple cube-shaped laminated object was fabricated using a commercially available laminated object fabrication device (product name: ProX DMP200, manufactured by 3DSystem). That is, a laser beam was irradiated onto the powder material laid flat, melting each layer, and this process was repeated to fabricate a cube-shaped object (30 mm long x 10 mm wide x 10 mm thick). The laser beam had an output of 300 W, a scanning speed of 300 mm / s, a pitch width of 0.1 mm, a layer thickness of 30 μm per layer, and the number of layers was 334.
[0106] After the layered manufacturing process, the obtained molded object was subjected to a heat treatment, that is, a sintering process was performed in a reduced pressure atmosphere (10 Pa) at 1320°C for 4 hours (continuously).
[0107] For the powder materials obtained in each of the Examples and Comparative Examples, XRD (X-ray diffraction) measurements using CuKα rays were performed before and after the laser beam irradiation. That is, XRD measurements were performed on the powder materials (granulated sintered particles) before the laser beam irradiation, and on the shaped objects after the laser beam irradiation and before the heat treatment. For the XRD measurements, an X-ray diffraction analyzer (RIGAKU, Ultima IV) was used, and CuKα rays (voltage 20 kV, current 10 mA) were used as the X-ray source, and the scan range was 2θ=10°-70°, scan speed: 10° / min, sampling width: 0.01°, divergence slit: 1°, divergence vertical limiting slit: 10 mm, scattering slit: 1 / 6°, light receiving slit: 0.15 mm, and offset angle: 0°. Figures 2-1(a)-(e) and Figures 2-2(f)-(h) show the XRD spectra of the powder materials obtained in Examples 1-5 and Comparative Examples 1-3 before and after the laser beam irradiation. Here, if a peak corresponding to the spectrum before the laser irradiation was observed in the peak of the XRD spectrum after the laser irradiation, the peak was determined to be a peak derived from the powder material. If a peak corresponding to the spectrum before the laser irradiation was not observed in the peak of the XRD spectrum after the laser irradiation, the peak was determined to be a peak other than the peak derived from the powder material. In this case, if the intensity of the peak other than the peak derived from the powder material is less than 1% of the intensity of the strongest peak in the XRD spectrum after the laser irradiation, the peak other than the peak derived from the powder material was determined to be "absent", and if it is 1% or more, it was determined to be "present".
[0108] In addition, the XRD spectra of the sintered bodies after heat treatment of the objects produced in each Example were also measured. No peaks other than those attributable to the powder material were observed in any of the sintered bodies.
[0109] The shaped object obtained in Example 1 and the sintered body obtained by heat-treating the shaped object were cut in a direction perpendicular to the lamination direction, and the cross sections were observed at a magnification of 1000 times using a scanning electron microscope (SEM; S-3000N, manufactured by Hitachi High-Technologies Corporation). Note that the observation of the cross sections of the shaped objects in this specification was carried out according to a standard method by embedding an evaluation sample of the shaped object in resin and exposing the cross section.
[0110] The results are shown in Figure 3(a). In the SEM images of (a1) the molded object and (a2) the sintered body, the black areas are areas where TiC exists, and the white areas are areas where Co exists.
[0111] The cross sections of the shaped object obtained in Comparative Example 3 and the sintered compact obtained by heat-treating the shaped object were also observed in the same manner. The results are shown in Fig. 3(b). In the SEM photographs of the (b1) shaped object and the (b1) sintered compact, the black areas are areas where Co exists, and the white areas are areas where WC exists.
[0112] The cross section of the sintered body after the heat treatment of the shaped object produced in each Example and Comparative Example was mirror-polished, and the Vickers hardness of the cross section was measured in accordance with JIS Z2244:2009. The Vickers hardness was measured using a microhardness tester (Shimadzu Corporation, HMV-1) and calculated from the indentation obtained when a diamond indenter with a facing angle of 136° was pressed with a test force of 0.2 kgf (1.96 N) for a holding time of 10 seconds. The Vickers hardness was measured at six points, and the arithmetic average value was taken as the hardness (Vickers hardness (HV)) of the shaped object (sintered body) after the heat treatment. The results are shown in Table 1 below.
[0113] [Table 1]
[0114] As shown in Figs. 2-1(a) to (e) and Table 1, the XRD spectrum of each of the molded objects produced in Examples 1 to 5 did not show any peaks other than the peaks derived from the powder material before the laser beam irradiation. For example, as shown in Fig. 2-1(a), a peak derived from TiC indicated by ◯ and a peak derived from Co indicated by △ were observed in the XRD spectrum of the molded object produced using the powder material of Example 1, and these peaks correspond to the peak derived from TiC and the peak derived from Co in the XRD spectrum of the powder material, respectively. In addition, no peaks other than those present in the XRD spectrum of the powder material were observed in the XRD spectrum of the molded object. This shows that the generation of a brittle phase due to the laser beam irradiation is suppressed in the molded object produced in Example 1. In the XRD spectrum of the molded object produced in Examples 2 to 5 shown in Figs. 2-1(b) to (e), no peaks other than those present in the XRD spectrum of the powder material were observed. Therefore, the XRD spectrum of the molded object does not show any peaks other than those derived from the powder material before the laser beam irradiation. Similarly, the shaped object produced in Example 6 did not show any peaks in the XRD spectrum other than those derived from the powder material before the laser beam irradiation (not shown). Furthermore, in the shaped objects of Examples 1, 2, and 4 to 6, the solid solubility of the carbide ceramics in the metal at 1250°C was 8 mass% or less. In such shaped objects, for example, as shown in FIG. 3(a1), a homogeneous and dense shaped object without cracks or chips can be obtained even without heat treatment. Furthermore, as shown in (a2), no noticeable grain growth is observed even when heat treatment is performed. And, as shown in Table 1, it was found that the shaped object (sintered body) after heat treatment exhibited excellent hardness.
[0115] In contrast, the objects produced in Comparative Examples 1 to 3 show peaks in the XRD spectrum other than the peak derived from the powder material before the laser beam irradiation, as shown by the arrows in Fig. 2-2(f) to (h). This is considered to indicate that a brittle phase is formed in the alloy structure of the carbide ceramic and the metal. Specifically, in the XRD spectrum of the object produced using the powder material of Comparative Example 3 in Fig. 2-2(h), a peak derived from Co3WC3, which is a reaction product of WC and Co, and a peak derived from W2C, which is a product of reduced carbon in WC, are observed. These peaks are not observed in the XRD spectrum of the powder material, and can be said to be peaks other than those derived from the powder material. In the object produced in Comparative Example 3, it is considered that a brittle phase such as the η phase is generated by the above-mentioned reaction products and products. In the XRD spectrum of the object produced using the powder material of Comparative Example 1 in Fig. 2-2(f), a peak derived from a product of reduced carbon in Cr3C2 is observed at the position indicated by the arrow. In the XRD spectrum of the molded object produced using the powder material of Comparative Example 2 in Figure 2-2(g), peaks derived from the reaction product of Mo2C and Co are observed at the positions indicated by the arrows. These peaks are considered to indicate the formation of a brittle phase in the alloy structure.
[0116] In Comparative Examples 1 to 3, the solubility of the carbide ceramics in the metal at 1250°C was more than 8% by mass. In such shaped articles, for example, as shown in FIG. 3(b1), a dense shaped article was not obtained. It was also found that sufficient densification could not be achieved even by carrying out a heat treatment, as shown in FIG. 3(b2). In such shaped articles, the hardness of the shaped article (sintered body) after the heat treatment was insufficient. [Explanation of symbols]
[0117] 10 Stacking Area 11 Wiper 12 Stock 13 Solidification means 14 Lift table 20 Powder material layer 21 Powder solidification layer.
Claims
1. A powder material for additive manufacturing comprising a carbide ceramic and a metal, the content of the metal is 8 to 43 volume % based on the total amount of the carbide ceramic and the metal; A powder material for additive manufacturing, in which the XRD spectrum of an object manufactured by additive manufacturing including laser beam irradiation does not contain any peaks other than those attributable to the powder material before laser beam irradiation.
2. A powder material for additive manufacturing comprising a carbide ceramic and a metal, the content of the metal is 8 to 43 volume % based on the total amount of the carbide ceramic and the metal; The powder material for additive manufacturing, wherein the solubility of the carbide ceramic in the metal at 1250°C is 8 mass% or less.
3. The powder material for additive manufacturing according to claim 1 or 2, wherein the carbide ceramic has a standard enthalpy of formation of -90 kJ / mol or less.
4. The powder material for additive manufacturing according to claim 1 or 2, wherein the melting point of the carbide ceramic is 2700°C or higher.
5. The powder material for additive manufacturing according to claim 1 or 2, wherein the carbide ceramic is one or more compounds selected from the group consisting of carbides of Group 4 elements and carbides of Group 5 elements.
6. The powder material for additive manufacturing according to claim 1 or 2, wherein the metal is one or more selected from the group consisting of cobalt, nickel, and iron.
7. The powder material for additive manufacturing according to claim 1 or 2, which is composed of granulated and sintered particles in which the carbide ceramics and the metal are mixed.
8. A method for manufacturing a molded object, comprising the steps of: performing additive manufacturing using the powder material for additive manufacturing according to claim 1 or 2.
9. The method for manufacturing a molded object according to claim 8 , wherein the additive manufacturing comprises melting and solidifying the powder material by irradiating it with laser light.
Citation Information
Patent Citations
Molding material to be used for powder laminate molding
JP2017113952A
Molding material to be used for powder laminate molding
JP2017114716A
Molding material to be used for powder laminate molding
JP2017115194A
Powder material to be used in powder lamination shaping and powder lamination shaping method using same
WO2015194678A1